The prevalence of deciduous tooth wear in six-year-old children and its relationship with potential explanatory factors - Rios, Daniela (2007)
Purpose: To evaluate the prevalence and aetiological factors involved with wear of deciduous teeth. Materials and Methods: A convenience sample of 356 children (aged 6 years old) was selected at Bauru, SP (Brazil). Clinical examinations were carried out by 1 examiner (Kappa = 0.87), using the Tooth Wear Index (G0-G4). A questionnaire addressing the aetiological factors of tooth wear was applied to parents. Results: Wear on the incisors was diagnosed in 34.8% of children (91.1% G1 and 6.4% G2); 78.1% presented wear in canines (64.7% G1 and 33.1% G2); and 40.7% in molars (89.6% G1 and 9.0% G2). No significant correlation was observed between gastro-oesophageal reflux, toothbrushing habits, or consumption of citrus fruits/soft drinks and the presence of tooth wear for all groups of teeth. The wear showed correlation with the presence of bruxism for canines and with the habit of holding drinks in the mouth before swallowing for incisors (Chi-square test, p>0.05). Conclusions: The findings indicate that the wear of incisors could be considered physiological for this age. Further longitudinal studies should be conducted in order to measure the wear in canines and molars in the period close to their replacement by permanent teeth.